Fishery and biology of threadfin bream, Nemipterus mesoprion from Mangalore-Malpe - Zacharia, P U; Nataraja, G D (Indian Journal of Fisheries, 2011)
Fishery and biology of threadfin bream, Nemipterus mesoprion from Mangalore-Malpe